APPLICATION OF COLLOCATION IN AL-QUR`AN - Fatihah, Imroatul (EL-IBTIKAR, 2017)
AbstractThe word collocation and collocation of sentence structure both have a role in giving meaning. Word will not produce meaning without any relation with other words. The word relation is a combination commonly used by native speakers. Native language speakers will naturally combine familiar words using trained intuition. Where accuracy in combining word pairs is called by linguists as collocation.This study concludes that collocation at the level of the word in the Quran produces a polysemic meaning. This means that every word in the Quran has a lot of meaning that requires a relationship between words with a harmonious combination. Because of each word has a precision in the use of a sentence. Example word Ø§ÙØÙØ¯, this word is synonymous with the word Ø§ÙÙØ¯Ø and also the word Ø§ÙØ«ÙØ§Ø¡. These three words have the meaning of praise and appreciation of a beauty, pleasure or other that is immaterial. As an expression of praise to Allah the exact combination of three words is using the word Ø§ÙØÙØ¯. The word Ø§ÙØÙØ¯ also contains meaning, Ø§ÙØ´ÙØ± but the use of the word Ø§ÙØÙØ¯ is only used to express gratitude to God, while to express gratitude to the creature by using the word Ø´ÙØ±.Keywords: Collocation, Linguistic, Al-Qurâan